Răspuns :
[tex]x = 5[/tex]
[tex]a + b = 13[/tex]
[tex]a)3x + 7a + 7b = 3x + 7(a + b)[/tex]
[tex] = 3 \times 5 + 7 \times 13[/tex]
[tex] = 15 + 91[/tex]
[tex] = 106[/tex]
[tex]b)xa + xb - 50 = x(a + b) - 50[/tex]
[tex] = 5 \times 13 - 50[/tex]
[tex] = 65 - 50[/tex]
[tex] = 15[/tex]
[tex]c)10x + 4a + 4b = 10x + 4(a + b)[/tex]
[tex] = 10 \times 5 + 4 \times 13[/tex]
[tex] = 50 + 52[/tex]
[tex] = 102[/tex]
[tex]d)(4a + 4b - 2x)(2a + 2b + x)[/tex]
[tex] = [4(a + b) - 2x][2(a + b) + x][/tex]
[tex] = (4 \times 13 - 2 \times 5)(2 \times 13 + 5)[/tex]
[tex] = (52 - 10)(26 + 5)[/tex]
[tex] = 42 \times 31[/tex]
[tex] = 1302[/tex]
[tex]a + b = 13[/tex]
[tex]a)3x + 7a + 7b = 3x + 7(a + b)[/tex]
[tex] = 3 \times 5 + 7 \times 13[/tex]
[tex] = 15 + 91[/tex]
[tex] = 106[/tex]
[tex]b)xa + xb - 50 = x(a + b) - 50[/tex]
[tex] = 5 \times 13 - 50[/tex]
[tex] = 65 - 50[/tex]
[tex] = 15[/tex]
[tex]c)10x + 4a + 4b = 10x + 4(a + b)[/tex]
[tex] = 10 \times 5 + 4 \times 13[/tex]
[tex] = 50 + 52[/tex]
[tex] = 102[/tex]
[tex]d)(4a + 4b - 2x)(2a + 2b + x)[/tex]
[tex] = [4(a + b) - 2x][2(a + b) + x][/tex]
[tex] = (4 \times 13 - 2 \times 5)(2 \times 13 + 5)[/tex]
[tex] = (52 - 10)(26 + 5)[/tex]
[tex] = 42 \times 31[/tex]
[tex] = 1302[/tex]
x = 5
a + b = 13
__________
a. 3 ⋅ x + 7 ⋅ a + 7 ⋅ b
b. x ⋅ a + x ⋅ b– 50
c. 10 ⋅ x + (4 ⋅ a + 4 ⋅ b)
d. (4 ⋅ a + 4 ⋅ b– 2 ⋅ x) ⋅ (2 ⋅ a + 2 ⋅ b + x)
a. 3 ⋅ x + 7 ⋅ a + 7 ⋅ b =
pas ₁: Se dă factor comun pe 7.
3 ⋅ x + 7 ⋅ (a + b ) =
pas ₂: Se înlocuieşte.
3 ⋅ 5 + 7 ⋅ 13=
pas₃: Se rezolvă.
15+ 91=
106
b. x ⋅ a + x ⋅ b– 50=
pas ₁: Se dă factor comun pe x.
x ⋅ (a + b )- 50=
pas ₂: Se înlocuieşte.
5·13- 50=
pas₃: Se rezolvă.
65-50=
15
c. 10 ⋅ x + (4 ⋅ a + 4 ⋅ b) =
pas ₁: Se dă factor comun pe 4.
10 ⋅ x + 4 ⋅ (a+ b) =
pas ₂: Se înlocuieşte.
10 ⋅ 5 + 4 ⋅ 13=
pas₃: Se rezolvă.
50+ 52=
102
d. (4 ⋅ a + 4 ⋅ b– 2 ⋅ x) ⋅ (2 ⋅ a + 2 ⋅ b + x) =
pas ₁: Se dă factor comun pe 4 şi 2.
[4 ⋅ (a + b– 2 ⋅ x)] ⋅ [2 ⋅ (a + b) + x] =
pas ₂: Se înlocuieşte.
(4 ⋅ 13 -2·5)·(2⋅ 13+ 5)=
pas₃: Se rezolvă.
(52-10)·(26+ 5)=
42·31=
1 302